Crystallization kinetics of chain extended poly(lactic acid)/clay nanocomposites. Issue 11 (5th July 2014) - Liu, Bengang; Du, Zhongjie; Wang, Xiangdong; Xin, Fei; Liu, Wei
<x xml:space="preserve">Abstract</x> The poly(lactic acid)/clay nanocomposites (PLACNs) were prepared by melt mixing method, then multiepoxide chain extender (CE) was added into PLACNs to induce the branched structure of poly(lactic acid) (PLA) chains. The nonisothermal cold crystallization and isothermal melting crystallization of PLA, PLACNs, and chain extended PLACNs (CEPLACNs) were characterized by DSC and studied by Avrami analysis. The results showed that the inducing of clay and CE affected the crystallization behavior of PLA in different way. Adding CE increased the overall crystallinity of PLA at cooling process, but clay had an opposite effect. Besides that, the addition of CE and clay increased the crystal nuclei number due to the heterogeneous nucleation mechanism. According to the crystallization kinetics study, the inducing of clay almost no effect on the crystal growth rate of PLA, but the branched structure had a pronounced effect for improving crystal growth rate of PLA. POLYM. COMPOS., 36:2123–2134, 2015. © 2014 Society of Plastics Engineer